Pengaruh Produk Terhadap Keputusan Pembelian Online Pakaian di Kalangan Mahasiswa IKIP Muhammadiyah Maumere - Elisabet Dei; Nur Chotimah; Muhammad Taufik Arifin (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2024)
This study aims to find the effect of the Product on Online Purchasing Decisions for Clothing Among Students of IKIP Muhammadiyah Maumere. This research was carried out at the IKIP Muhammadiyah Maumere Campus. The population in this Study were Students of IKIP Muhammadiyah Maumere who made purchases of clothes Online. The sample in this study amounted to 73 people. The sampling technique used is a random sampling technique with the term random sampling. This study uses a quantitative descriptive approach. all statements are valid,reliable,normal,linear,and heteroscedastic. based on the results of simple linear regression calculations obtained purchasing decisions = 33,537+0,691 (Product).